PRAKTISI NOTARIS SEBAGAI PENGAJAR UNTUK MELAHIRKAN LULUSAN YANG MUMPUNI KAITANNYA DENGAN PROGRAM MBKM - Djaja, Benny (Jurnal Bakti Masyarakat Indonesia, 2022)
One of the requirements for Public Notary appointment according to UUJN is the completion of a graduate study program in notary education. The growing number of universities of ering the Notary Masters Study Program (MKn) gives rise to some problems: the absence of curriculum standards, the lack of competence of the teaching staf s to produce professional Notaries, and the increasing number of graduates not in proportion to the available quota for new appointments. Making available adequate legal instruments and professionals in accordance with the written regulations to respond to the needs of the community requires good cooperation between legal institutions and education institutions, in this case particularly the MKn program. The elaborations in this writing aims to understand the responsibilities of notary as public of icer especially in light of the Professional Organization Regulation, as well as the necessity to incorporate practitioners as part of the lecturers board in the MKn Study Program, in line with the Government program Merdeka Belajar, Kampus Merdeka (MBKM). MKn Program aims to produce professional and competent Notary candidates pursuant to the Notary Association Regulation. Following their graduation, ef orts to achieve said aims are resumed through the obligations of prospective notaries to participate in individual internship, communal internship, as well as seminars/ conferences and socializations. Hereunder, the authors describe a community service activity carried out in the form of empowerment and socialization, targeted to improve the understanding of candidate notaries in an event called Special Members Selection Briefing organized by the West Jakarta Regional Management of the Indonesian Notary Association. Following the dissemination of materials concerning Notaries as part of the legal profession and a public of icer pursuant to UUJN, Notaries as professional educator within Prodi MKn, and their responsibilities, these activities are wrapped up with a Q&A session and evaluation. The intended outcome of these activities are scientific publications in an ISSN-registered journal and a selected mass media outlet. ABSTRAK: Persyaratan untuk dapat diangkat menjadi Notaris sesuai dengan UUJN salah satunya yaitu telah menyelesaikan pendidikan spesialis Kenotariatan. Banyaknya Perguruan Tinggi penyelenggara program studi Magister Kenotariatan (Prodi MKn) menimbulkan permasalahan, antara lain tidak adanya standar kurikulum, kurangnya kompetensi pengajar untuk melahirkan Notaris yang profesional, dan meningkatnya jumlah lulusan pendidikan Notaris yang tidak seimbang dengan jumlah formasi pengangkatan Notaris. Untuk mendukung terciptanya perangkat atau profesi hukum yang sesuai dengan aturan tertulis dan menjawab kebutuhan masyarakat, diperlukan kerjasama yang harmonis antara institusi hukum dengan lembaga pendidikan hukum, yaitu Prodi MKn. Penelitian ini bertujuan untuk memahami pertanggungjawaban Notaris sebagai pejabat publik, khususnya terkait Peraturan Perkumpulan Notaris, dan pentingnya kehadiran praktisi Notaris sebagai bagian dari tim pengajar di Prodi MKn sesuai dengan tujuan program Merdeka Belajar Kampus Merdeka (MBKM) yang dicanangkan Pemerintah untuk perguruan tinggi. Prodi MKn bertujuan untuk membentuk calon Notaris yang profesional dan mempunyai kompetensi mumpuni sesuai dengan Peraturan Perkumpulan organisasi Notaris, yaitu Ikatan Notaris Indonesia (INI). Pasca kelulusan, tujuan tersebut dilanjutkan melalui kewajiban magang (perorangan), magang bersama, serta mengikuti seminar/penyuluhan hukum. Dalam tulisan ini, Penulis menguraikan pelaksanaan pengabdian masyarakat dalam bentuk penyuluhan dan sosialisasi untuk meningkatkan pemahaman para calon Notaris dalam Pembekalan Seleksi Anggota Luar Biasa Wilayah Jakarta Barat. Setelah pemberian materi mengenai Notaris sebagai bagian dari profesi hukum dan pejabat publik sesuai dengan UUJN, Notaris sebagai pendidik profesional dalam Prodi MKn, dan tanggung jawab Notaris, kegiatan ini diakhiri dengan tanya jawab dan evaluasi. Rencana luaran yang dihasilkan dari kegiatan ini berupa publikasi ilmiah pada jurnal ber-ISSN dan media massa.